A reflexivity exercise: interviews and political representation of women (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
In this paper, I will focus on the making of interviews as a work strategy. I do not propose, then, to reflect in the abstract, but based on the historical research I produced from the interviews.I will attend the representative dimension of the concept of citizenship. I will expose the lessons learned in the process of constructing my research problem about how women became political citizens in Argentina between 40’s and 50’s.
Keywords: Methodology; Interviews; Gender; Political citizenship argentina